2008
DOI: 10.1007/s11060-008-9659-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiologic response of medulloblastoma cell lines: involvement of β-catenin?

Abstract: Medulloblastoma (MB) is the most common brain malignancy in children. Whole neural axis irradiation is the treatment of choice, but it often results in long-term neurocognitive and developmental impairment. Only insights into MB biology will lead to improved therapeutic outcome. Wingless (WNT) signalling deregulation occurs in up to 25% of sporadic tumors, but the specific role of nuclear beta-catenin and its involvement in the radioresponse remains unsettled. Therefore we studied the gamma-radiation response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…D283MED and DAOY cells were harvested 8,16,24,29,40 and 48 h after the addition of LiCl and total protein extracts were prepared as previously described (29), using the following extraction buffer: 1% Triton, 10% glycerol, 50 mM Tris pH 7.4, 150 mM NaCl, 2 mM EDTA pH 8.0, 2 mM MgCl 2 , 50 mM sodium fluoride, 10 mM sodium pyrophosphate, 1 mM sodium orthovanadate and Complete EDTA-free (Roche Diagnostic; Indianapolis, IN) 2X.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…D283MED and DAOY cells were harvested 8,16,24,29,40 and 48 h after the addition of LiCl and total protein extracts were prepared as previously described (29), using the following extraction buffer: 1% Triton, 10% glycerol, 50 mM Tris pH 7.4, 150 mM NaCl, 2 mM EDTA pH 8.0, 2 mM MgCl 2 , 50 mM sodium fluoride, 10 mM sodium pyrophosphate, 1 mM sodium orthovanadate and Complete EDTA-free (Roche Diagnostic; Indianapolis, IN) 2X.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear proteins were extracted 24, 29, 32, 40 and 48 h after the addition of LiCl, as previously described (29). Aliquots of nuclear pellets were stained with hematoxylineosin (HE) and observed under a light microscope (Carl Zeiss GmbH; Oberkochen, Germany) to verify the lack of cytoplasmic contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, even though McMillan et al 43 demonstrated in 1993 that medulloblastomas are very radiosensitive, invading cells seem to be relatively resistant. This has prompted a few research teams to investigate ways by which to predict and/or increase the radio-sensitivity of these tumours [44][45][46][47] . In general these studies have demonstrated (1) that different cell lines differ in their degree of radio-sensitivity [48][49][50] ; and (2) that cell radio-sensitivity can, in fact, be altered by a variety of external means 45,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Salaroli et al 44 studied the gamma-radiation response of two MB cell lines, both from a cellular and molecular point of view, and discovered that a p53 wild-type cell line was more sensitive to ionizing radiation than a p53 mutated line. And Tsuboi et al 50 isolated two mutant clones from a single medulloblastoma, one radiosensitive (OS-3) and one resistant (OR-5), but also found that the administration of 5mM of caffeine generated greater cytotoxicity in the latter cells.…”
Section: Discussionmentioning
confidence: 99%